2022
DOI: 10.22603/ssrr.2021-0237
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Outcome Measures Evaluating the Health-Related Quality of Life of Children and Adolescents with Idiopathic Scoliosis and Scheuermann's Kyphosis: A Literature Review

Abstract: Adolescent idiopathic scoliosis (AIS) and Scheuermann's kyphosis (SK) are the most common types of spinal deformities in adolescents, and both have substantial ramifications on health-related quality of life (HRQoL) parameters. Various questionnaires have been developed to assess HRQoL in age-group populations with spinal deformity. Nevertheless, there remains a lack of consensus across the literature as to which instrument is the most suitable for evaluating the HRQoL of this cohort. Thus, this literature rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Another limitation is that individuals’ quality of life was assessed with SRS-22. It has been reported that SRS-22 may have a ceiling effect in the assessment of quality of life in IS [ 53 ]. Therefore, in future studies, it may be more appropriate to assess quality of life in adult individuals with IS using the Brace Questionnaire or the Italian Spine Youth Quality of Life questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that individuals’ quality of life was assessed with SRS-22. It has been reported that SRS-22 may have a ceiling effect in the assessment of quality of life in IS [ 53 ]. Therefore, in future studies, it may be more appropriate to assess quality of life in adult individuals with IS using the Brace Questionnaire or the Italian Spine Youth Quality of Life questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the positive effect of Schroth physiotherapy scoliosis-specific exercise (PSSE) on slowing or interrupting the progression of AIS has been supported by randomized controlled trials (cited frequency 3rd, Among the questionnaire studies of HRQOL, five papers selected the Scoliosis Research Society 22-item questionnaire SRS-22 (centrality 2nd, 4th, and 5th studies), the Bad Sobernheim Stress Questionnaire (BSSQbrace) (centrality 6th study), and the Spinal Appearance Questionnaire. The SRS-22 patient questionnaire has been shown to be an effective tool for the clinical assessment of patients with AIS, especially for patients who may undergo surgical interventions (43), and the widespread use of the SRS-22 in non-English-speaking countries requires its cross-cultural adaptation. The 2nd study of centrality translated and culturally adapted the SRS-22 questionnaire into Spanish, and testing demonstrated adequate internal consistency and excellent reproducibility of the Spanish version of the SRS-22 patient questionnaire.…”
Section: Analysis Of Research Hotspots In Key Literaturementioning
confidence: 99%